Identification and characterization of Putative Virulence genes and gene clusters in Aeromonas Hydrophila PPD134/91 - Yu, H.B.; Zhang, Y.L.; Lau, Y.L.; Yao, F.; Vilches, S.; Merino, S.; Tomas, J.M.; Howard, S.P.; Leung, K.Y. (2005)
Aeromonas hydrophila is a gram-negative opportunistic pathogen of animals and humans. The pathogenesis of A. hydrophila is multifactorial. Genomic subtraction and markers of genomic islands (GIs) were used to) identify putative virulence genes in A. hydrophila PPD134/91. Two rounds of genomic subtraction led to the identification of 22 unique DNA fragments encoding 19 putative virulence factors and seven new open reading frames, which are commonly present in the eight virulence strains examined. In addition, four GIs were found, including O-antigen, capsule, phage-associated, and type III secretion system (TTSS) gene clusters. These putative virulence genes and gene clusters were positioned on a physical map of A. hydrophila PPD134/91 to determine their genetic organization in this bacterium. Further in vivo study of insertion and deletion mutants showed that the TTSS may be one of the important virulence factors in A. hydrophila pathogenesis. Further. more, deletions of multiple virulence factors such as S-layer, serine protease, and metalloprotease also increased the 50 lethal dose to the same level as the TTSS mutation (about 1 log) in a blue gourami infection model. This observation sheds light on the multifactorial and concerted nature of pathogenicity in A. hydrophila. The large number of putative virulence genes identified in this study will form the basis for further investigation of this emerging pathogen and help to develop effective vaccines, diagnostics, and novel therapeutics.